Feasibility Theory: A Resource-Munificence Model of Work Motivation and Behavior - Klein, Jonathan I. (Academy of Management Review, 1990)
A model is proposed that presents a curvilinear relationship between the feasibility of a task and motivation to perform it, to account for theory, research, and anecdotal evidence consistent with both a positive and negative relationship between the two variables. Feasibility is defined as resources available to perform the task, which are positively related to motivation when scarce and negatively related to motivation when abundant. This is because resource scarcity potentiates lower-order needs satisfied by resources, whereas resource abundance permits the indulgence of higher-order needs, including arousal, achievement, power, and affiliation, the satisfaction of which is maximized by task difficulty, which in turn is reduced by resources. Discussion focuses on perceptual determinants, motivational consequences, and behavioral outcomes of resource munificence, and implications for theory, research, and practice.